2021
DOI: 10.3389/fendo.2020.526332
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vertebral Bone Strength Using Finite Element Analysis for Opportunistic Osteoporosis Screening in Routine Multidetector Computed Tomography Scans—A Feasibility Study

Abstract: PurposeTo investigate the feasibility of using routine clinical multidetector computed tomography (MDCT) scans for conducting finite element (FE) analysis to predict vertebral bone strength for opportunistic osteoporosis screening.MethodsRoutine abdominal MDCT with and without intravenous contrast medium (IVCM) of seven subjects (five male; two female; mean age: 71.86 ± 7.40 years) without any bone disease were used. FE analysis was performed on individual vertebrae (T11, T12, L1, and L2) including the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The effective loading and boundary conditions are normally applied to simulate the effects of the adjacent bones and muscles. This kind of simplified method had been used to evaluate the biomechanics of human bones such as femur (Dhanopia & Bhargava, 2017), tibia (Abdul Wahab et al, 2020), humerus (Jabran et al, 2019), rib (Yates et al, 2021), and vertebra (Rayudu et al, 2021). Those finite element models could significantly reduce the modelling steps and computational time as compared to a musculoskeletal system model.…”
Section: Discussionmentioning
confidence: 99%
“…The effective loading and boundary conditions are normally applied to simulate the effects of the adjacent bones and muscles. This kind of simplified method had been used to evaluate the biomechanics of human bones such as femur (Dhanopia & Bhargava, 2017), tibia (Abdul Wahab et al, 2020), humerus (Jabran et al, 2019), rib (Yates et al, 2021), and vertebra (Rayudu et al, 2021). Those finite element models could significantly reduce the modelling steps and computational time as compared to a musculoskeletal system model.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high radiation levels preclude the use of QCT for pediatric research. Although QCT has become the standard 3D approach to assess vBMD at the proximal femur and lumbar spine, substantial efforts are underway to validate opportunistic screening based on clinical CT scans -that is, without a calibration phantom -for assessments of vBMD [16] and estimates of bone strength using FEA [16][17][18]. Cross-sections of coronal and sagittal reformations of QCT scans of the proximal femora and lumbar spine are shown in Fig.…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…Vertebral body, intervertebral disc, surrounding ligaments and muscles may be simulated by FEM models and may also be used to describe spine-related biomechanical particularities, as well as to analyze the stress allocation of the vertebral sections. As far as osteoporosis is concerned, there are numerous studies that have used FEM models to assess fracture risk, treatment comparison and biomechanics in the osteoporotic bones [54][55][56][57][58][59][60][61][62][63][64]. In particular, it is reported that nonlinear CT/FEA had better distinctive ability for vertebral fractures than lumbar spine BMD by DXA and QCT [55,59].…”
Section: Osteoporosismentioning
confidence: 99%